Pengaruh Penambahan NaCl sebagai Stress Agent dalam Kultivasi Sel Mikroalga Dunaliella tertiolecta ATCC 30929 terhadap Akulumasi Lipid Intrasel - Karseno Karseno; M. Takagi; T. Yoshida (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
Lipid composition of microalgae cell was affected by saline medium. Increasing of initial NaCI in modified NORO medium from 0.5 M to 1.0 M resulted in an increase of intracellular lipid content of Dunaliella tertiolecta ATCC 30929 cell from 60% to 67% (db). Loading of 0.5 M NaCI at a middle of logarithmic phase or 1.0 M at the end of logarithmic phase during the growth on the same medium increased intracellular lipid content to 70% (db). Addition of NaCI up to 2.0 M during the culture gave a high intracellular lipid content up to 77% (db) , although cell concentration was decreased to a half The temperature, light intensity, and aeration was adjusted at 30 Â°C, 150 mo1.11.m-2 (10.000 lux) and 250 ml/min CO2 enriched air (CO2 3%).